How to answer the question of error margin in forensic signature examination with a Bayesian approach? - Marquis, Raymond; Cadola, Liv; Mazzella, Williams David; Hicks, Tacha (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In 2011, a new Criminal Procedure Code was adopted in Switzerland. Since then, forensic handwriting experts more frequently face challenging questions from lawyers. These additional questions especially focus on the degree of certainty regarding the conclusions of the expert, and on the error margin of the signature analysis. The authors seek to address such issues in a scientific manner, in agreement with laws of probability. On the basis of a case, they present the likelihood ratio approach they have followed to evaluate their results, and a full Bayesian approach designed to explain the question of error. The questions of interest were solved with this framework and the use of numbers in a case specific way. The proposed answer aims to explain to the Court what is the probability of being wrong in case at hand. The approach followed is robust, logic and transparent and represents a practical way of addressing the error margin question.
Keywords: questioned documents; signature; interpretation; likelihood ratio; evaluation; Bayes’ theorem; error margin